FAVIPIRAVIR AND DEXAMETHASONE IN MANAGEMENT OF SARS-COV2 INFECTION: (PILOT STUDY) - Latief, M.; Shafi, O.; Hassan, Z.; Abbas, F. (International Journal of Medicine and Medical Research, 2021)
Background. The clinical presentation of Coronavirus disease 19 (COVID-19) varies from mild symptoms to severe illness including multiorgan dysfunction. Favipiravir is an antiviral agent which has been previously used for treatment of influenza and was recently approved for treatment of mild to moderate COVID-19 in India. Objective. The Objective of this study was to assess the role of Favipiravir and Dexamethasone in patients with COVID-19. Methods. A total of 17 patients were included in this observational study. The included patients were RT-PCR for SARS-Cov-2 positive with increased inflammatory markers. All patients received Antiviral therapy, Anticoagulation (Enoxaparin 0.4mg subcutaneous twice daily), Steroids (Dexamethasone 8mg daily for 5days and 4mg daily for 5 days). Viral clearance (time to RT-PCR negative), time to defervescence after antiviral therapy, time to become independent of Oxygen support was studied. Results. Fever, myalgias, dry cough and dyspnea were the commonest presentation of COVID-19. All of our patients had lymphopenia. In our study 11 (64.7%) patients had bilateral ground glass opacities on CT chest while 6 had consolidation in addition to ground glass opacities. In two patients, who required non-invasive ventilation, Favipiravir was stopped and these patients received Remdesivir for a total of 5 days. In patients who received Favipiravir only, the Median time to RT-PCR negative, defervescence and oxygen independence was 8,3 and 6 days respectively. Conclusion. Our observational study demonstrated improvement in the majority of patients with COVID-19 with use of Favipiravir. Additional studies are needed to compare the efficiency of Favipiravir with Remdesivir.